Rapid Generation of Cell Gradients by Utilizing Solely Nanotopographic Interactions on a Bio‐Inert Glass Surface1. Issue 11 (12th February 2014) - Yang, Gao; Cao, Yanhua; Fan, Junbing; Liu, Hongliang; Zhang, Feilong; Zhang, Pengchao; Huang, Chao; Jiang, Lei; Wang, Shutao
Abstract The control of cell gradients is critical for understanding many biological systems and realizing the unique functionality of biomimetic implants. Herein, we report a nanotopographic gradient strategy that can rapidly generate cell gradients on a nanodendritic silica substrate without any chemical modification. We can achieve controllable cell gradients within only half an hour of cell incubation solely induced by the topographic effect of the gradient nanodendrites. We also demonstrate that cell gradients can be modulated by the combination of nanotopographic and chemical gradients. The results reveal that the enhanced topographic interactions between the nanodentritic structure and nanoscaled filopodia of the cells mainly contribute to the generation of cell gradients.